TCF7L2 transcriptionally regulates Fgf15 to maintain bile acid and lipid homeostasis through gut‐liver crosstalk. Issue 3 (8th February 2022) - Bhat, Neha; Esteghamat, Fatemehsadat; Chaube, Bal Krishna; Gunawardhana, Kushan; Mani, Mitra; Thames, Clay; Jain, Dhanpat; Ginsberg, Henry N.; Fernandes‐Hernando, Carlos; Mani, Arya
Abstract: FGF19/FGF15 is an endocrine regulator of hepatic bile salt and lipid metabolism, which has shown promising effects in the treatment of NASH in clinical trials. FGF19/15 is transcribed and released from enterocytes of the small intestine into enterohepatic circulation in response to bile‐induced FXR activation. Previously, the TSS of FGF19 was identified to bind Wnt‐regulated TCF7L2 /encoded transcription factor TCF4 in colorectal cancer cells. Impaired Wnt signaling and specifical loss of function of its coreceptor LRP6 have been associated with NASH. We, therefore, examined if TCF7L2/TCF4 upregulates Fgf19 in the small intestine and restrains NASH through gut‐liver crosstalk. We examined the mice globally overexpressing, haploinsufficient, and conditional knockout models of TCF7L2 in the intestinal epithelium. The TCF7L2 +/− mice exhibited increased plasma bile salts and lipids and developed diet‐induced fatty liver disease while mice globally overexpressing TCF7L2 were protected against these traits. Comprehensive in vivo analysis revealed that TCF7L2 transcriptionally upregulates FGF15 in the gut, leading to reduced bile synthesis and diminished intestinal lipid uptake. Accordingly, Vilin Creert2 ; Tcf7L2 fl/fl mice showed reduced Fgf19 in the ileum, and increased plasma bile. The global overexpression of TCF7L2 in mice with metabolic syndrome‐linked LRP6 R611C substitution rescued the fatty liver and fibrosis in the latter. Strikingly, the hepatic levels of TCF4 were reduced and CYP7a1 was increased in human NASH, indicating the relevance of TCF4‐dependent regulation of bile synthesis to human disease. These studies identify the critical role of TCF4 as an upstream regulator of the FGF15‐mediated gut‐liver crosstalk that maintains bile and liver triglyceride homeostasis.